Falling in Love with Virtual Reality Art: A New Perspective on 3D Immersive Virtual Reality for Future Sustaining Art Consumption. Issue 4 (25th February 2022) - Kim, Yunju; Lee, Heejun
ABSTRACT: Many art activities have been trialed in 360-degree virtual reality (VR) and this has become an increasingly representative way toward sustainable consumption of art. However, understanding audience responses to the VR art remains a matter of debate and investigation. By employing the uses and gratifications (U&G) approach, this study explores motives for and consequences of watching 360-degree VR art. The identified motives are three dimensions: pursuing learning from entertainment, pursuing social conformity, and pursuing convenience . Among the three use motives, it was found that pursuing learning from entertainment is the most significant factor influencing audiences' transportation experience while watching 360-degree VR art, and audiences' innovativeness functions as a moderator in the relationship between transportation and the attitude toward the VR content. The theoretical and practical implications of this study are discussed.